Impact of employees' behaviors in the workplace. - Emrah Atar (Cambridge Scholars Publishing, 2022)
The rapid development of economic globalisation has caused enterprises to have a higher demand for high-quality employees in order to achieve competitive advantages. This has brought a significant challenge to human resource management. As employees are the imperative group in enterprises for gaining profit and maintaining regular operation, it is critical to raise their enthusiasm for work. Their creativity and subjective initiative could be fully activated, and the profit determination would increase if the appropriate motivating methods were utilised.As such, this collection offers detailed.